Opicapone, a Novel Catechol-O-methyl Transferase Inhibitor, for Treatment of Parkinson's Disease "Off" Episodes - Amnon A. Berger; Ariel Winnick; Jonathan Izygon; Binil M. Jacob; Jessica S. Kaye; Rachel J. Kaye; Elisa E. Neuchat; Adam M. Kaye; Edward S. Alpaugh; Elyse M. Cornett; Andrew H. Han; Alan D. Kaye (Health Psychology Research)
Parkinson's Disease (PD) is a common neurodegenerative disorder and the leading cause of disability. It causes significant morbidity and disability through a plethora of symptoms, including movement disorders, sleep disturbances, and cognitive and psychiatric symptoms. The traditional pathogenesis theory of PD involves the loss of dopaminergic neurons in the substantia nigra (SN). Classically, treatment is pursued with an assortment of medications that are directed at overcoming this deficiency with levodopa being central to most treatment plans. Patients taking levodopa tend to experience "off episodes" with decreasing medication levels, causing large fluctuations in their symptoms. These off episodes are disturbing and a source of morbidity for these patients. Opicapone is a novel, peripherally acting Catechol-O-methyl transferase (COMT) inhibitor that is used as adjunctive therapy to carbidopa/levodopa for treatment and prevention of "off episodes." It has been approved for use as an adjunct to levodopa since 2016 in Europe and has recently (April 2020) gained FDA approval for use in the USA. By inhibiting COMT, opicapone slows levodopa metabolism and increases its availability. Several clinical studies demonstrated significant improvement in treatment efficacy and reduction in duration of "off episodes." The main side effect demonstrated was dyskinesia, mostly with the 100mg dose, which is higher than the approved, effective dose of 50mg. Post-marketing surveillance and analysis are required to further elucidate its safety profile and contribute to patient selection. This paper reviews the seminal and latest evidence in the treatment of PD "off episodes" with the novel drug Opicapone, including efficacy, safety, and clinical indications.